Seasonal dynamics of Sulfur dioxide and Sulfate aerosols over India: Insights from Sentinel-5P and MERRA-2 datasets - Priya J S; Krishnakumar V; Sabna Rahim (Bulletin of Atmospheric Science and Technology, 2026)

Aerosol and cloud characteristics during two extreme periods over Kerala - J. S. Priya; V. Krishnakumar (Meteorology and Atmospheric Physics, 2026)

Decline of Acropora spp. in the Saudi Waters of the Arabian Gulf: Insights from Thirteen Years of Reef Surveys - Sudhanshu Dixit; Reynaldo T. Lindo; Rommel H. Maneja; Ace Vincent B. Flandez; Jinoy Gopalan; Thiyagarajan Duraisamy; Goutham Sambath; Yasir Y. Asiri; Mubarak S. Al-Jedani; Periyadan K. Krishnakumar; Karuppasamy P. Manikandan; Thadickal V. Joydas; et al. (Ocean Science Journal, 2026)

Spatial heterogeneity of microplastic pollution and associated emerging contaminants in tropical estuarine environments: Novel insights into distribution, bioavailability, and ecological risk - Vijayalekshmi Padmachandran Aiswriya; P.S. Nishmitha; Kochuparambil Ajayaghosh Akhilghosh; Karunakaran Malavika; Swathy Krishna; Muthukumar Muthuchamy; S. Krishnakumar; Anbazhagi Muthukumar (Marine Pollution Bulletin, 2026)

Assessment of the reliable pollution indicators in the continental aquatic systems of a developing country in the context of global environmental sustainability: insights into the sedimentology and geochemistry of the Karuvannur River, India - S. Siji; A. Krishnakumar; K. Anoop Krishnan (Environmental Geochemistry and Health, 2026)

A curcumin–resveratrol–carnosic acid complex mitigates brain–gut axis disruption in a rodent model of repeated mild traumatic brain injury - Mohind C Mohan; Anjana A S; Deepa Azhchath Vasu; Yadukrishnan M B; Aneesa P A; Tara Sudhadevi; Krishnakumar I M; Baby Chakrapani P S (Metabolic Brain Disease, 2026)

Rare-earth (Er3+) modified ZnO photocatalyst: Dual action in organic dye degradation under UV/solar light and microbial suppression - S. Sargunavathi; S. Balamurugan; Balakrishna Avula; T. Abisheik; N. Lakshman Kumar; V. Pandiyan; Vimalraj. V; Arun Thirumurugan; Gabriela Sandoval-Hevia; Abdullah K. Alanazi; Krishnakumar Balu (Journal of Water Process Engineering, 2026)

Exploring the anticancer potential of Tinospora cordifolia with computational insights into EGFR inhibition - G. Asha; S. Lekshmi; K.P. Najmathunnisa; T. Rajva; V. Krishnakumar; K. P. Safna Hussan (In Silico Pharmacology, 2025)

Geochemistry and contamination metrics of the tropical agricultural soils in Karuvannur Basin, India, with special reference to environmental sustainability - S. Siji; A. Krishnakumar; Gayathri Nair; K. Anoop Krishnan (Environmental Geochemistry and Health, 2025)

Modulation of COX-2, 5-LOX, and cytokine signalling by Carica papaya L. Leaf cultivar ‘Red Lady’ flavonoids in inflammation: in-vitro and in-silico insights - Sheethal S. Kumar; Chandran Remya; K. Krishnakumar; Evelyn Maria; K. V. Dileep; Mathew John (Natural Product Research, 2025)

P30-57 Towards a Defined Approach to Assess Pesticides for their Potential to Cause Parkinsonian Neurodegeneration - J. Nyffeler; T. Tal; S. Schildknecht; B. Viviani; B. Tanja; Q. Fu; R. Owen; A.E.V. Krishnakumar; I. Mangas; A. Terron (Toxicology Letters, 2025)

The Impact of Quality of Sleep and Effect of Sleep Apnea on Periodontal Health - Swathi Devarajan; P. Sreelakshmi; Divya Kumar; Deepak Moses Ravindran; Dhanadivya Krishnakumar; S. K. Balaji (Sleep and Vigilance, 2025)

Correction to: Physico‑chemical characteristics of fresh faecal matter from a residential apartment: a short‑term study conducted at Thiruvananthapuram, Kerala, India - Saurabh Sakhre; Reshma Anil S; Ajantha S; Ritesh Vijay; Krishnakumar Bhaskaran (Environmental Monitoring and Assessment, 2025)

Drought Vulnerability Assessment Using GIS and Remote Sensing Techniques: A Case Study in Part of Coimbatore, Tamil Nadu, India - S. Krishnakumar; V. Sreevidhya; S. Vivek; V. Priya (Journal of the Indian Society of Remote Sensing, 2025)

Study on the Seasonal and Spatial Variations of Cirrus Parameters, Radiative Characteristics and Precipitation over the Indian Subcontinent - J. S. Priya; V. Krishnakumar; Sona Baiju; R. G. Sreelekshmi; Afna Shoufeer (Journal of the Indian Society of Remote Sensing, 2025)

Physico-chemical characteristics of fresh faecal matter from a residential apartment: a short-term study conducted at Thiruvananthapuram, Kerala, India - Saurabh Sakhre; Reshma Anil S; Ajantha S; Ritesh Vijay; Krishnakumar Bhaskaran (Environmental Monitoring and Assessment, 2024)

Exploring the cytoprotective potential of flavonoid fraction from Carica papaya L. Cultivar ‘Red Lady' Leaf: Insights into Nrf2 activation via in-vitro and in-silico approaches - Sheethal S. Kumar; Krishnakumar K; Evelyn Maria; Mathew John (South African Journal of Botany, 2024)

Marine pollution and ecological degradation—issues and challenges - S. Krishnakumar; D. Satheesh Herbert Singh; Babu Nallusamy; M. A. Mohammed Aslam (Environmental Science and Pollution Research, 2024)

Distribution and Characterization of Microplastics Along the Coastal Shoreline of Thiruvananthapuram District, Kerala, India - H. S. Arjun; Vijayalekshmi Padmachandran Aiswriya; Muthukumar Muthuchamy; S. Krishnakumar; Satheesh Herbert Singh; Anbazhagi Muthukumar (Water, Air, & Soil Pollution, 2024)

Evaluation of potential trace element contamination and ecological risks of beach sediments, Andaman and Nicobar Archipelago, India - S. Anbalagan; S. Krishnakumar; K. Kasilingam; Satheesh Herbert Singh; D. Pradhap; P. Saravanan; K. Neelavannan; N.S. Magesh; S. Selvakumar (Total Environment Advances, 2024)

Seasonal variability in trace metal concentrations in sediment samples from the Puducherry and Cuddalore coasts of Tamil Nadu, India - K. Sanjai Gandhi; D. Pradhap; S. Krishnakumar; V. Kanagaraj (Total Environment Advances, 2024)

Investigating radiation profiles and conducting risk assessment for ecological and environmental components on Vaan and Koswari islands in the Tuticorin group of islands, India - S. J. Athul Krishnan; P. Nishanth; ATVR Venkatraman; S. Krishnakumar; Marckasagayam Priyadharshini; Mohamed Saiyad Musthafa (Environmental Monitoring and Assessment, 2024)

Exploring the possibility of a proprietary black cumin oil extract as a Dual Orexin Receptor Antagonist in restoring stress-sleep balance on stress-induced sleep deprived animals - Saneha OR; Priya Krishna; Syam Das S; Krishnakumar IM; Litty Joseph (PharmaNutrition, 2023)

Antihemolytic activity of flavonoids from butanolic extract of Carica papaya L. cultivar ‘Red Lady’ leaf - Sheethal S. Kumar; Krishnakumar K; Mathew John (Food and Humanity, 2023)

Occurrence, distribution and sources of petroleum contamination in reef-associated sediments of the Gulf of Mannar, India - Diptimayee Behera; S. Krishnakumar; Ambili Anoop (Marine Pollution Bulletin, 2023)

A dominant mode in the first phase of the Asian summer monsoon rainfall: role of antecedent remote land surface temperature - Subodh Kumar Saha; Yongkang Xue; Sujith Krishnakumar; Ismaila Diallo; Yashas Shivamurthy; Tetsu Nakamura; Qi Tang; Hemantkumar S. Chaudhari (Climate Dynamics, 2023)

Oral bioavailability and neuroprotective effect of a novel food-grade formulation of fisetin using fenugreek-galactomannan hydrogel scaffolds - K. Athira; S. Syam Das; Andrew Swick; I.M. Krishnakumar; A. Abdul Vahab (PharmaNutrition, 2023)

Emerging pollutants: impact on environment, management, and challenges - S. Krishnakumar; D. Satheesh Herbert Singh; Prince S. Godson; Salom Gnana Thanga (Environmental Science and Pollution Research, 2022)

Effectiveness of Site-Specific Management Practices on the Amelioration of Soil Acidity in the Coconut Growing Entisol and Ultisol of Humid Tropics - Jeena Mathew; A. Abdul Haris; S. Indhuja; V. Krishnakumar; K. M. Nair; Ravi Bhat; K. S. Anil Kumar (Journal of Soil Science and Plant Nutrition, 2022)

Coral annual growth band impregnated microplastics (Porites sp.): a first investigation report - S. Krishnakumar; S. Anbalagan; S. M. Hussain; R. Bharani; Prince Samuel Godson; S. Srinivasalu (Wetlands Ecology and Management, 2021)

Monitoring of heavy metal contamination in Netravati river basin: overview of pollution indices and risk assessment - S. Gayathri; K. Anoop Krishnan; A. Krishnakumar; T. M. Vishnu Maya; Vinu V. Dev; Sibin Antony; V. Arun (Sustainable Water Resources Management, 2021)

First report on the association of ‘Candidatus Phytoplasma asteris’ with lethal wilt disease of coconut (Cocos nucifera L.) in India - Merin Babu; S. Thangeswari; A. Josephrajkumar; V. Krishnakumar; A. Karthikeyan; V. Selvamani; Mol Daliya; Vinayaka Hegde; H. P. Maheswarappa; Anitha Karun (Journal of General Plant Pathology, 2021)

In Vitro Seedlings as Dynamic Explants for Establishment of Root Cultures of Pyrenacantha volubilis Hook. for Camptothecin Production - S. Hima; C. K. Midhu; G. Krishnakumar; K. Satheeshkumar (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2020)

Comparative neuroprotective effects of native curcumin and its galactomannoside formulation in carbofuran-induced neurotoxicity model - Sindhu E. R.; Binitha P. P.; Saritha S. Nair; Balu Maliakel; Ramadasan Kuttan; Krishnakumar I. M. (Natural Product Research, 2020)

Changing Characteristics of Droughts over Kerala, India: Inter-Annual Variability and Trend - Abhilash S.; E. K. Krishnakumar; P. Vijaykumar; A. K. Sahai; B. Chakrapani; Girish Gopinath (Asia-Pacific Journal of Atmospheric Sciences, 2019)

Curcumin–galactomannoside complex inhibits pathogenesis in Ox-LDL-challenged human peripheral blood mononuclear cells - Sangeeth Saji; S. Asha; Periyappurath Jose Svenia; M. Ratheesh; S. Sheethal; S. Sandya; I. M. Krishnakumar (Inflammopharmacology, 2018)

Role of lutoid membrane transport and protein synthesis in the regeneration mechanism of latex in different Hevea clones - S. Sreelatha; Sheela P. Simon; V. C. Mercykutty; Kavitha K. Mydin; R. Krishnakumar; K. Annamalainathan; James Jacob (Acta Physiologiae Plantarum, 2016)

Genotype–phenotype analysis of von Hippel–Lindau syndrome in fifteen Indian families - Narendranath Vikkath; Sindhu Valiyaveedan; Sheela Nampoothiri; Natasha Radhakrishnan; Gopal S. Pillai; Vasantha Nair; Ginil Kumar Pooleri; Georgie Mathew; Krishnakumar N. Menon; Prasanth S. Ariyannur; Ashok B. Pillai (Familial Cancer, 2015)

Evaluation of Antitumor Activity of Hesperetin-Loaded Nanoparticles Against DMBA-Induced Oral Carcinogenesis Based on Tissue Autofluorescence Spectroscopy and Multivariate Analysis - Krishnamoorthy Gurushankar; Shaiju S. Nazeer; Ramapurath S. Jayasree; Narendran Krishnakumar (Journal of Fluorescence, 2015)

SHARP: genome-scale identification of gene–protein–reaction associations in cyanobacteria - S. Krishnakumar; Dilip A. Durai; Pramod P. Wangikar; Ganesh A. Viswanathan (Photosynthesis Research, 2013)

Groundwater quality assessment using WQI and GIS techniques, Dindigul district, Tamil Nadu, India - N. S. Magesh; S. Krishnakumar; N. Chandrasekar; John Prince Soundranayagam (Arabian Journal of Geosciences, 2013)

Screening of chemopreventive effect of naringenin-loaded nanoparticles in DMBA-induced hamster buccal pouch carcinogenesis by FT-IR spectroscopy - N. Krishnakumar; N. K. Sulfikkarali; S. Manoharan; R. Madhavan Nirmal (Molecular and Cellular Biochemistry, 2013)

Evaluation of mucoadhesive nanoparticle based nasal vaccine - D. Krishnakumar; D. Kalaiyarasi; J. C. Bose; K. S. Jaganathan (Journal of Pharmaceutical Investigation, 2012)

Integrated approach for demarcating subsurface pollution and saline water intrusion zones in SIPCOT area: a case study from Cuddalore in Southern India - S. Sankaran; S. Sonkamble; K. Krishnakumar; N. C. Mondal (Environmental Monitoring and Assessment, 2012)

Internal Tides in the Coastal Waters of NE Arabian Sea: Observations and Simulations - P. V. Hareesh Kumar; S. Lekshmi; P. S. V. Jagadeesh; K. Anilkumar; G. V. Krishnakumar; A. D. Rao (Marine Geodesy, 2010)

Seasonal and interannual variations of oceanographic conditions off Mangalore coast (Karnataka, India) in the Malabar upwelling system during 1995–2004 and their influences on the pelagic fishery - P. K. KRISHNAKUMAR; G. S. BHAT (Fisheries Oceanography, 2008)
Mangalore coast is well known for its multi‐species and multi‐gear fisheries and the fishery and oceanographic features of this region is a true representation of the Malabar upwelling system. Ten years of study (1995–2004) of oceanographic parameters has been carried out from the inshore waters off Mangalore to understand their seasonal and interannual variations and influences on the pelagic fishery of the region. Attempt has been also made to understand the influence of local and global environmental conditions on the alternating patterns of abundance between the Indian mackerel and oil sardine from the area. Field‐ and satellite‐derived oceanographic data have shown that coastal upwelling occurs during July–September with a peak in August resulting in high nutrient concentrations and biological productivity along the coast. Nearly 70% of the pelagic fish catch, dominated by oil sardine and mackerel, was obtained during September–December, during or immediately after the upwelling season. Catches of scombroid fishes were significantly related to cold Sea Surface Temperature, while such relationships were not observed for sardines and anchovies. Significant positive correlations were observed between the ENSO events (MEI) and seawater temperature from the study area. The extreme oceanographic events associated with the cold La Niña, which preceded the exceptional 1997–98 El Niño event, were responsible for the collapse of the pelagic fishery, especially the mackerel fishery along the southwest coast of India (Malabar upwelling system). Coinciding with the collapse of the mackerel fishery, oil sardine populations revived during 1999–2000 all along the southwest coast of India. Tolerance of oil sardine to El Niño / La Niña events and the low predatory pressure experienced by their eggs and larvae due to the collapse of mackerel population might have resulted in its population revival.

Identification, characterization and utilization of EST-derived genic microsatellite markers for genome analyses of coffee and related species - Ramesh K. Aggarwal; Prasad S. Hendre; Rajeev K. Varshney; Prasanna R. Bhat; V. Krishnakumar; Lalji Singh (Theoretical and Applied Genetics, 2007)

Monitoring Trace Metal Contaminants in Green Mussel, Perna viridis from the Coastal Waters of Karnataka, Southwest Coast of India - Geetha Sasikumar; P. K. Krishnakumar; G. S. Bhat (Archives of Environmental Contamination and Toxicology, 2006)

Biomarkers of environmental contaminants in field population of green mussel (Perna viridis) from Karnataka–Kerala coast (South West coast of India) - P. K. Krishnakumar; Geetha Sasikumar; G. S. Bhat; D. P. K. Asokan (Ecotoxicology, 2006)